Operationalising equity in ecosystem-based fisheries management - Riley Bibaud; Tom Mullier; Matthew Ashley; Holly Niner; Lauren Stewart; Siân Rees (Marine Policy, 2026)

Eight recommendations to enhance biodiversity outcomes of nature-based solutions at multiple scales - Charles B. van Rees; Collin VanBuren; Lori A. Han; Andrew Altieri; Matt Bilskie; James E. Byers; Jon Calabria; Matthew L. Chambers; Daniel J. Coleman; Katie Foster; Aliza Leit; Alec Nelson; et al. (Journal of Environmental Management, 2026)

Integrated modelling reveals widespread distribution of invasive wild pigs across Australia - Matthew W. Rees; David J. Mitchell; Katherina Ng; Sandra K. Parsons; Kirstin M. Proft; Scott D. Foster; David Peel; Zachary Amir; Tom Bruce; Matthew S. Luskin; Jens G. Froese (Biological Conservation, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

An assessment model for linking changes in pelagic habitat state to impacts on human wellbeing - Matthew P. Faith; Siân E. Rees; Angus Atkinson; Mike Best; Eileen Bresnan; Michelle J. Devlin; Matthew M. Holland; Holly J. Niner; Clare Ostle; Paul Tett; Abigail McQuatters-Gollop (Marine Policy, 2025)

The palaeogeography of the Bass Strait land-bridge, a vital zone of human and biological connectivity across southeastern Australia - David M. Kennedy; Ali Jalali; Bruno David; Matthew C. McDowell; Rachel A. Nanson; Ashleigh J. Rogers; Russell Mullett; Joanna Fresløv; Jessie Birkett-Rees; Juliet Sefton; Daniel Ierodiaconou (Quaternary Science Reviews, 2025)

Every move matters: physical activity, walking, sedentary behavior, and endometrial cancer survival - Lauren C. Bates-Fraser; Matthew Masters; Clara Bodelon; Lauren E. McCullough; Marissa M. Shams-White; Alpa V. Patel; Erika Rees-Punia (Cancer Causes & Control, 2025)

Ferrite magnets do not deter blue sharks (Prionace glauca) from bait strikes in behavioural trials - Sol Lucas; Gonzalo Araujo; Rosalind M.K. Bown; Mark Johns; Samuel Matthews; Emma Nicol; Kristian J. Parton; Richard Rees; Gemma Scotts; Victoria Walker; Emma Williams; Per Berggren (Fisheries Research, 2025)

Putting numbers to a metaphor: A Bayesian Belief Network with which to infer Soil Quality and Health - Kirsty L. Hassall; Joanna Zawadzka; Alice E. Milne; Ronald Corstanje; James A. Harris; A. Gordon Dailey; Aidan M. Keith; Margaret J. Glendining; S.P. McGrath; Lindsay C. Todman; Paul Alexander; Philippa Arnold; et al. (European Journal of Agronomy, 2025)

Quantifying the effects of extreme flooding on coastal reef fishes - Matthew J. Rees; Nathan A. Knott; David Harasti; Timothy C. Ingleton; Hamish A. Malcolm; Rachel Przeslawski (Ecology, 2025)
The ecological impacts of extreme floods to benthic ecosystems in oceanic environments remain unclear, as events are difficult to observe and quantify. Between 2020 and 2022, an unusually long La Niña resulted in substantial flooding across southeastern Australia. Major floods in the Hawkesbury‐Nepean River led to an unprecedented flood plume extending ~70 km offshore to depths of ~50 m, exposing coastal biodiversity to rare environmental conditions. Here, we use long‐term monitoring data to quantify the impacts of large‐scale flooding to coastal rocky reef fishes. Flooding reduced the total abundance and species richness of reef fishes by 50% and 13%, respectively. Declines were primarily due to reductions in the abundance of planktivores (−75%) and benthic invertivores (−40%). Assemblages at reference locations isolated from large rivers were stable across the study period, indicating observed patterns were in response to floods. Surveys 1‐year post flooding signaled that benthic invertivores were beginning to recover but not planktivores. Our results demonstrate the detrimental impacts of extreme flooding to some coastal rocky reef fishes. Given projected increases in the severity and frequency of rainfall due to climate change, our findings suggest that extreme flooding may compromise ecosystem functions and services provided by rocky reef fish in a future climate.

Acute and partial life-cycle toxicity of a tri-polymer blend of microplastics in the copepod Acartia tonsa - Zara L.R. Botterell; Rachel L. Coppock; Alessio Gomiero; Penelope K. Lindeque; Stefania Piarulli; Thomas Rees; Lisbet Sørensen; Matthew Cole (Environmental Pollution, 2025)

Maize genotypes foster distinctive bacterial and fungal communities in the rhizosphere - Xinya Wen; Jie Lu; Jun Zou; Joann K. Whalen; Shaoliang Lei; Matthew Tom Harrison; Robert M. Rees; Cairistiona F.E. Topp; Zhenwei Song; Fu Chen; Xiaogang Yin (Agriculture, Ecosystems & Environment, 2025)

Optimizing N rate in wheat-maize rotation to match long-term and inter-seasonal N turnover for high yield and sustainability using STICS - Datong Zhang; Shuaijie Shen; Zhiyuan Bai; Matthew Tom Harrison; Ke Liu; Robert M. Rees; Cairistiona F.E. Topp; Jun Zou; Yuhao Yang; Zhenwei Song; Haotian Chen; Xiaogang Yin (Field Crops Research, 2025)

Drivers of soybean-based rotations synergistically increase crop productivity and reduce GHG emissions - Ying Yang; Jun Zou; Wenhai Huang; Jørgen Eivind Olesen; Wenjie Li; Robert M. Rees; Matthew Tom Harrison; Biao Feng; Yupeng Feng; Fu Chen; Xiaogang Yin (Agriculture, Ecosystems & Environment, 2024)

Consequences of Juvenile Fish Movement and Seascape Connectivity: Does the Concept of Nursery Habitat Need a Rethink? - Daniel S. Swadling; Nathan A. Knott; Matthew D. Taylor; Matthew J. Rees; Gwenael Cadiou; Andrew R. Davis (Estuaries and Coasts, 2024)
Estuarine and adjacent inshore habitats have long been recognised as important nursery areas for fishes before they disperse to coastal habitats. Assessing nursery function supports spatial and fisheries management, yet work commonly focusses on singular habitat types. Re-considering how juvenile fish connect habitats may improve our understanding of nursery function and the scales that recruits are supplied to coastal fisheries. This study quantified the juvenile movements of two harvested fishes in south-eastern Australia, luderick ( Girella tricuspidata ) and yellowfin bream ( Acanthopagrus australis ). Acoustic tags were used to track 33 luderick and 20 yellowfin bream from seagrass meadows for up to ~400 days in Jervis Bay Marine Park. Both species had relatively small home ranges (< 7 km 2 ) and exhibited site attachment to seagrass meadows where they were released. Most luderick and yellowfin bream were detected moving 100’s metres to kilometres to reefs adjacent to seagrass, although these movements were not habitat shifts. Rather, reef-ward movements represented repeated visits that lasted days to months before fish returned to seagrass, suggesting that these movements may be explorations in search of suitable adult habitat. Strong retention within an existing marine reserve was observed, with only five of 33 fish tagged within reserves crossing the boundary into fished waters. Overall, our results demonstrate that juvenile fish use and connect multiple habitat types during their movements. These findings support the broadening of the nursery concept from single habitats to a mosaic of functionally connected habitat patches (dubbed ‘seascape nurseries’).

Fox control and fire influence the occurrence of invasive predators and threatened native prey - Matthew W. Rees; Brendan A. Wintle; Alan Robley; Jack H. Pascoe; Mark Le Pla; Emma K. Birnbaum; Bronwyn A. Hradsky (Biological Invasions, 2024)
It can be challenging to distinguish management impacts from other population drivers, including ‘natural’ processes and co-occurring threats. However, disentangling processes is important, particularly when management may have unintended consequences, such as mesopredator release. We explored the effects of long-term, broadscale poison-baiting programs on the distribution of red foxes Vulpes vulpes (targeted invasive predator), feral cats Felis catus (unmanaged invasive competitor) and two of their threatened native prey in two fire-affected regions of south-eastern Australia. We synthesised data from 3667 camera-trap deployments at 1232 sites (172,052 trap-nights), combining experimental manipulation of foxes and fire with space-for-time approaches. Fox control effectiveness—in terms of decreased probability of fox occurrence and increased probability of prey occurrence—depended on the duration and intensity of the poison-baiting program. The effects of fox control on prey occurrence also varied between the two native prey species: fox control was strongly beneficial to the long-nosed potoroo Potorous tridactylus but had no measurable effect on southern brown bandicoot Isoodon obesulus occurrence. Feral cat occupancy tended to be higher in landscapes with long-term fox control, although we found no effect of fox-bait density on fine-scale cat occurrence. Time since fire (0–80 years) was associated with the occurrence of each study species, but its association with invasive predators also differed among vegetation types. Invasive predators and altered fire regimes are key, often overlapping, biodiversity threats. Our work highlights the importance of fine-scale monitoring and consideration of multiple drivers in distribution models to develop effective, tailored conservation strategies.

Wheat cultivar replacement drives soil microbiome and microbial cooccurrence patterns - Jie Lu; Xiaogang Yin; Kangcheng Qiu; Robert M. Rees; Matthew Tom Harrison; Fu Chen; Xinya Wen (Agriculture, Ecosystems & Environment, 2024)

Cumulative effects of multiple stressors impact an endangered seagrass population and fish communities - Matthew J. Rees; Nathan A. Knott; Karen L. Astles; Daniel S. Swadling; Greg J. West; Adrian M. Ferguson; Jason Delamont; Peter T. Gibson; Joseph Neilson; Gavin F. Birch; Tim M. Glasby (Science of The Total Environment, 2023)

An evidence base of ecosystems services provided by diadromous fish in the European Atlantic Area - Matthew Ashley; Arantza Murillas; Angela Muench; Cristina Marta-Pedroso; Lynda Rodwell; Sian Rees; Emma Rendle; Tea Bašić; Gordon H. Copp; Estibaliz Díaz; David J. Nachón; Patrick Lambert; et al. (Ecosystem Services, 2023)

Nature-based solutions for leveed river corridors - Matthew L. Chambers; Charles B. van Rees; Brian P. Bledsoe; David Crane; Susana Ferreira; Damon M. Hall; Rod W. Lammers; Craig E. Landry; Donald R. Nelson; Matt Shudtz; Burton C. Suedel (Anthropocene, 2023)

Anchor scour from shipping and the defaunation of rocky reefs: A quantitative assessment - Allison Broad; Matthew Rees; Nathan Knott; Daniel Swadling; Matthew Hammond; Tim Ingleton; Bradley Morris; Andrew R. Davis (Science of The Total Environment, 2023)

Optimizing crop rotation increases soil carbon and reduces GHG emissions without sacrificing yields - Yuhao Yang; Jinsong Ti; Jun Zou; Yao Wu; Robert M. Rees; Matthew Tom Harrison; Wenxin Li; Wenhai Huang; Suya Hu; Ke Liu; Xinya Wen; Fu Chen; et al. (Agriculture, Ecosystems & Environment, 2023)

Effects of human footprint and biophysical factors on the body‐size structure of fished marine species - Nestor E. Bosch; Jacquomo Monk; Jordan Goetze; Shaun Wilson; Russell C. Babcock; Neville Barrett; Jock Clough; Leanne M. Currey‐Randall; David V. Fairclough; Rebecca Fisher; Brooke A. Gibbons; David Harasti; et al. (Conservation Biology, 2022)
Marine fisheries in coastal ecosystems in many areas of the world have historically removed large‐bodied individuals, potentially impairing ecosystem functioning and the long‐term sustainability of fish populations. Reporting on size‐based indicators that link to food‐web structure can contribute to ecosystem‐based management, but the application of these indicators over large (cross‐ecosystem) geographical scales has been limited to either fisheries‐dependent catch data or diver‐based methods restricted to shallow waters (

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Inter-laboratory automation of the in vitro micronucleus assay using imaging flow cytometry and deep learning - John W. Wills; Jatin R. Verma; Benjamin J. Rees; Danielle S. G. Harte; Qiellor Haxhiraj; Claire M. Barnes; Rachel Barnes; Matthew A. Rodrigues; Minh Doan; Andrew Filby; Rachel E. Hewitt; Catherine A. Thornton; et al. (Archives of Toxicology, 2021)
The in vitro micronucleus assay is a globally significant method for DNA damage quantification used for regulatory compound safety testing in addition to inter-individual monitoring of environmental, lifestyle and occupational factors. However, it relies on time-consuming and user-subjective manual scoring. Here we show that imaging flow cytometry and deep learning image classification represents a capable platform for automated, inter-laboratory operation. Images were captured for the cytokinesis-block micronucleus (CBMN) assay across three laboratories using methyl methanesulphonate (1.25–5.0 μg/mL) and/or carbendazim (0.8–1.6 μg/mL) exposures to TK6 cells. Human-scored image sets were assembled and used to train and test the classification abilities of the “DeepFlow” neural network in both intra- and inter-laboratory contexts. Harnessing image diversity across laboratories yielded a network able to score unseen data from an entirely new laboratory without any user configuration. Image classification accuracies of 98%, 95%, 82% and 85% were achieved for ‘mononucleates’, ‘binucleates’, ‘mononucleates with MN’ and ‘binucleates with MN’, respectively. Successful classifications of ‘trinucleates’ (90%) and ‘tetranucleates’ (88%) in addition to ‘other or unscorable’ phenotypes (96%) were also achieved. Attempts to classify extremely rare, tri- and tetranucleated cells with micronuclei into their own categories were less successful (≤ 57%). Benchmark dose analyses of human or automatically scored micronucleus frequency data yielded quantitation of the same equipotent concentration regardless of scoring method. We conclude that this automated approach offers significant potential to broaden the practical utility of the CBMN method across industry, research and clinical domains. We share our strategy using openly-accessible frameworks.

Increased connectivity and depth improve the effectiveness of marine reserves - Jordan S. Goetze; Shaun Wilson; Ben Radford; Rebecca Fisher; Tim J. Langlois; Jacquomo Monk; Nathan A. Knott; Hamish Malcolm; Leanne M. Currey‐Randall; Daniel Ierodiaconou; David Harasti; Neville Barrett; et al. (Global Change Biology, 2021)
Marine reserves are a key tool for the conservation of marine biodiversity, yet only ~2.5% of the world's oceans are protected. The integration of marine reserves into connected networks representing all habitats has been encouraged by international agreements, yet the benefits of this design has not been tested empirically. Australia has one of the largest systems of marine reserves, providing a rare opportunity to assess how connectivity influences conservation success. An Australia‐wide dataset was collected using baited remote underwater video systems deployed across a depth range from 0 to 100 m to assess the effectiveness of marine reserves for protecting teleosts subject to commercial and recreational fishing. A meta‐analytical comparison of 73 fished species within 91 marine reserves found that, on average, marine reserves had 28% greater abundance and 53% greater biomass of fished species compared to adjacent areas open to fishing. However, benefits of protection were not observed across all reserves (heterogeneity), so full subsets generalized additive modelling was used to consider factors that influence marine reserve effectiveness, including distance‐based and ecological metrics of connectivity among reserves. Our results suggest that increased connectivity and depth improve the aforementioned marine reserve benefits and that these factors should be considered to optimize such benefits over time. We provide important guidance on factors to consider when implementing marine reserves for the purpose of increasing the abundance and size of fished species, given the expected increase in coverage globally. We show that marine reserves that are highly protected (no‐take) and designed to optimize connectivity, size and depth range can provide an effective conservation strategy for fished species in temperate and tropical waters within an overarching marine biodiversity conservation framework.

Rapidly assessing cobenefits to advance threat‐management alliances - Matthew W. Rees; Josie Carwardine; Andrew Reeson; Jennifer Firn (Conservation Biology, 2020)
Conservation strategies aimed at reducing threats to biodiversity can have significant implications for multiple sectors in a socioeconomic system, but these cobenefits are often poorly understood. For example, many of the threats to native species also impede agricultural production, yet agriculture is typically perceived as in competition with conservation objectives. Although a comprehensive, multiobjective decision analysis is usually beyond the scope and capacity of conservation decision makers, failing to incorporate key socioeconomic costs and benefits into conservation decision‐making processes can result in missed opportunities for diversifying outcomes and creating cost‐sharing multisectoral partnerships. We devised a straightforward and readily interpretable approach to incorporate cobenefits into a threat‐management prioritization approach. We used it to analyze the agricultural cobenefits of implementing 9 invasive animal management strategies designed to ensure the persistence of 148 threatened species across Australia's Lake Eyre Basin over 50 years. A structured elicitation process with 24 participants (scientists, land managers, agriculturalists, and other stakeholders) was used to collect information on each strategy, including costs, technical and social feasibility, benefits to native threatened species, and cobenefits to agricultural production systems. The costs of targeted invasive animal management to save threatened species across the basin (AU$33 million/year) outweighed the overall benefits to the agricultural industry (estimated AU$226 million/year). The return on investment for these management strategies varied substantially when agricultural cobenefits were considered alongside threatened species benefits and showed synergies and challenges. Our approach demonstrates the value of incorporating cobenefits of conservation actions into cost‐effectiveness analyses to guide potential investment and partnerships and to diversify implementation pathways.

Finding rockpool fishes: a quantitative comparison of non-invasive and invasive methods for assessing abundance, species richness and assemblage structure - Marian Y. L. Wong; Paul Gordon; Kai C. Paijmans; Matthew J. Rees (Environmental Biology of Fishes, 2019)

Provisioning of bioavailable carbon between the wet and dry phases in a semi-arid floodplain - Darren S. Baldwin; Gavin N. Rees; Jessica S. Wilson; Matthew J. Colloff; Kerry L. Whitworth; Tara L. Pitman; Todd A. Wallace (Oecologia, 2013)

Impacts of inundation and drought on eukaryote biodiversity in semi‐arid floodplain soils - Darren S. Baldwin; Matthew J. Colloff; Gavin N. Rees; Anthony A. Chariton; Garth O. Watson; Leon N. Court; Diana M. Hartley; Matthew j. Morgan; Andrew J. King; Jessica S. Wilson; Michael Hodda; Christopher M. Hardy (Molecular Ecology, 2013)
Floodplain ecosystems are characterized by alternating wet and dry phases and periodic inundation defines their ecological character. Climate change, river regulation and the construction of levees have substantially altered natural flooding and drying regimes worldwide with uncertain effects on key biotic groups. In southern A ustralia, we hypothesized that soil eukaryotic communities in climate change affected areas of a semi‐arid floodplain would transition towards comprising mainly dry‐soil specialist species with increasing drought severity. Here, we used 18S r RNA amplicon pyrosequencing to measure the eukaryote community composition in soils that had been depleted of water to varying degrees to confirm that reproducible transitional changes occur in eukaryotic biodiversity on this floodplain. Interflood community structures (3 years post‐flood) were dominated by persistent rather than either aquatic or dry‐specialist organisms. Only 2% of taxa were unique to dry locations by 8 years post‐flood, and 10% were restricted to wet locations (inundated a year to 2 weeks post‐flood). Almost half (48%) of the total soil biota were detected in both these environments. The discovery of a large suite of organisms able to survive nearly a decade of drought, and up to a year submerged supports the concept of inherent resilience of Australian semi‐arid floodplain soil communities under increasing pressure from climatic induced changes in water availability.

Global analysis of satellite tracking data shows that adult green turtles are significantly aggregated in Marine Protected Areas - Rebecca Scott; David J. Hodgson; Matthew J. Witt; Michael S. Coyne; Windia Adnyana; Janice M. Blumenthal; Annette C. Broderick; Ali Fuat Canbolat; Paulo Catry; Stephane Ciccione; Eric Delcroix; Creusa Hitipeuw; et al. (Global Ecology and Biogeography, 2012)
Aim Tracking technologies are often proposed as a method to elucidate the complex migratory life histories of migratory marine vertebrates, allowing spatially explicit threats to be identified and mitigated. We conducted a global analysis of foraging areas of adult green turtles ( Chelonia mydas ) subject to satellite tracking ( n = 145) and the conservation designation of these areas according to International Union for Conservation of Nature criteria. Location The green turtle has a largely circumtropical distribution, with adults migrating up to thousands of kilometres between nesting beaches and foraging areas, typically in neritic seagrass or algal beds. Methods We undertook an assessment of satellite tracking projects that followed the movements of green turtles in tropical and subtropical habitats. This approach was facilitated by the use of the Satellite Tracking and Analysis Tool ( http://www.seaturtle.org ) and the integration of publicly available data on Marine Protected Areas (MPAs). Results We show that turtles aggregate in designated MPAs far more than would be expected by chance when considered globally (35% of all turtles were located within MPAs) or separately by ocean basin (Atlantic 67%, Indian 34%, Mediterranean 19%, Pacific 16%). Furthermore, we show that the size, level of protection and time of establishment of MPAs affects the likelihood of MPAs containing foraging turtles, highlighting the importance of large, well‐established reserves. Main conclusions Our findings constitute compelling evidence of the world‐wide effectiveness of extant MPAs in circumscribing important foraging habitats for a marine megavertebrate.

Public Lands Management Issues - Patrick Davis; Robert Malmsheimer; Eddie Bevilacqua; Terry Haines; Craig Wilcox; Robert Lefevre; Dan Rees; Tom St. Clair; Eric Miller; Terry Craigg; Paul Adams; Douglas Osborne; et al. (Journal of Forestry, 2011)
389Humans are responsible for nearly seventy thousand wildfires in the US each year, and human-caused fires have burned more than 2 million acres in five of the past ten years. Wildfires are a major contributor to US greenhouse gas emissions, adding 126.4 million metric tons of carbon dioxide into the atmosphere each year. These emissions can be significantly reduced with improved wildfire management strategies. This research examines the connection between human-caused fire proximity to physical characteristics, criminal activities, and other factors within National Forests. It presents a spatial pattern model that predicts the likelihood of fire ignition location based on physical attributes, such as: the spatial location of fire ignition crimes and other crimes on national forests, and the spatial location of national forest physical characteristics (e.g., roads, trails, recreational/unique resources, etc.). This research will present natural resource managers with practical applications of spatial analysis techniques utilizing GIS, as well as help public land managers target and deploy personnel in areas most prone to human fire ignitions during times of high fire risk.

Developing carbon budgets for UK agriculture, land-use, land-use change and forestry out to 2022 - Dominic Moran; Michael MacLeod; Eileen Wall; Vera Eory; Alistair McVittie; Andrew Barnes; R. M. Rees; Cairistiona F. E. Topp; Guillaume Pajot; Robin Matthews; Pete Smith; Andrew Moxey (Climatic Change, 2011)

Principles and application of an in vivo swine assay for the determination of arsenic bioavailability in contaminated matrices - Matthew Rees; Lloyd Sansom; Allan Rofe; Albert L. Juhasz; Euan Smith; John Weber; Ravi Naidu; Tim Kuchel (Environmental Geochemistry and Health, 2009)